Developing smallholder farming system - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Raising and sustaining productivity of smallholder farming systems in the Tropics by Willem C Beets 1990 755pp Hardback US$65.00 ISBN 974 85676 1 Paperback US$39.00 ISBN 974 85676 4 8 AgBe Publishing, PO Box 9125, 1800 GC Alkmaar, THE NETHERLANDS